2022
DOI: 10.1002/jbio.202100239
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation and photodynamic therapy applied after electrocauterization for skin healing optimization in rats

Abstract: Photobiomodulation-PBM and Photodynamic Therapy-PDT have been used to induce healing. However, the effects of these therapies on skin-lesions induced by electrocautery are unknown, aiming at more favorable clinical and esthetic results. Electrocauterization was done in 78-female Wistar-rats using a system that includes an electrocautery and red-LED. The groups were: No injury, Injury, Injury + ALA (topical 5-aminolevulinic acid application), Injury + LED and Injury + ALA + LED (topical ALA application followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This indicated that low‐dose ALA‐PDT could regulate the wound healing process by regulating the polarization of macrophages. Lately, the effects of low‐dose ALA‐PDT on the skin healing process after electrocauterization in Wistar‐rats was investigated [68]. This study showed that lower number of inflammatory cells after 2nd day, greater IL‐10 and higher concentration of antioxidants (SOD and GSH) after 7th day after treated with 3% ALA and 36 J/cm 2 light dose in the wound caused by electrocauterization.…”
Section: Low‐dose Ala/mal‐pdt In Wound Healingmentioning
confidence: 99%
“…This indicated that low‐dose ALA‐PDT could regulate the wound healing process by regulating the polarization of macrophages. Lately, the effects of low‐dose ALA‐PDT on the skin healing process after electrocauterization in Wistar‐rats was investigated [68]. This study showed that lower number of inflammatory cells after 2nd day, greater IL‐10 and higher concentration of antioxidants (SOD and GSH) after 7th day after treated with 3% ALA and 36 J/cm 2 light dose in the wound caused by electrocauterization.…”
Section: Low‐dose Ala/mal‐pdt In Wound Healingmentioning
confidence: 99%